Contemporary commentators on J.S. MILL’S account of women's socio-political issues - Átila Amaral Brilhante; Francisco José Sales Rocha (Ethic@: an International Journal for Moral Philosophy)
This article is purported to show that most of J.S. Mill’s contemporary commentators failed to situate his account of women’s issues in the broder context of his political thought. In view of this, they did not see the fact that Mill supported institutional changes in order to enfranchise women and allow married women to own property and benefit from higher education, on the grounds that such changes were important in transforming marriage into a relationship between equals based on friendship and cooperation. This would cause families to become the main locus of education for citizenship and renew societies by maximizing the poll of intelectual resources available with women in public life and render them directly resposible for their choice before society. Thus, accountability is at the haert of Mill’s account of women’s socio-political  issues.